2017
DOI: 10.1371/journal.pone.0188074
|View full text |Cite
|
Sign up to set email alerts
|

Indications and determinants of caesarean section delivery: Evidence from a population-based study in Matlab, Bangladesh

Abstract: Background and methodsCaesarean section (C-section) is a major obstetric intervention for saving lives of women and their newborns from pregnancy and childbirth related complications. Un-necessary C-sections may have adverse impact upon maternal and neonatal outcomes. In Bangladesh there is paucity of data on clinical indication of C-section at population level. We conducted a retrospective study in icddr,b Health and Demographic Surveillance System (HDSS) area of Matlab to look into the indications and determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
151
2
14

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(190 citation statements)
references
References 47 publications
23
151
2
14
Order By: Relevance
“…This present study found that 18.5% of women who delivered in health facilities 5 years preceding the survey delivered their babies through CS, a figure that exceeds the threshold of 5-15% recommended by WHO [7]. This corroborates the findings in previous studies in low-and -middle income countries such as Pakistan [1], Egypt, [11], Bangladesh [12], Ethiopia [31], India [32], Jordan [33] and Tanzania [34]. An improved propensity toward available medical interventions and continued discouragement of VD after previous CS may have added to the recent increase in CS rates as noted in other countries [35].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This present study found that 18.5% of women who delivered in health facilities 5 years preceding the survey delivered their babies through CS, a figure that exceeds the threshold of 5-15% recommended by WHO [7]. This corroborates the findings in previous studies in low-and -middle income countries such as Pakistan [1], Egypt, [11], Bangladesh [12], Ethiopia [31], India [32], Jordan [33] and Tanzania [34]. An improved propensity toward available medical interventions and continued discouragement of VD after previous CS may have added to the recent increase in CS rates as noted in other countries [35].…”
Section: Discussionsupporting
confidence: 91%
“…Those aged 45-49 had higher odds of CD compared to those aged [15][16][17][18][19]. Findings of the current study, which involved data from a wider coverage of women across Ghana show evidence that advanced maternal age is a higher risk factor for CS and that the extent of the risk surges with advancement in maternal age, a finding that is corroborated in other studies [1,11,12,28,29,[37][38][39]. Berkowitz et al [40] reiterated that advanced maternal age is generally believed to be associated with increased risk for adverse pregnancy outcome.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Selected studies suggest that the overall cesarean section rate is higher than global recommendations. A retrospective survey of an area of Dhaka, Bangladesh identified a 35% cesarean delivery rate with only 1.4% conducted due to absolute maternal indications [32]. According to data produced by Save the Children (2019) the cesarean section rate in private facilities is approximately 80% and has increased by 51% over the past two years [33].…”
Section: Mode Of Deliveries and Outcomesmentioning
confidence: 99%